Business Model Iteration System and Method for Energy Internet - Lin LIU; Suxiu LI; Hua ZHANG; Xifeng ZHANG; Yingqi LIU; Xingtong CHEN (Zhongguo dianli)
The quick advancement of energy consumption reform and digital economy brings about higher requirements for transformation and development of energy and power enterprises and business model innovation of energy Internet. The business model also needs dynamic innovation, iteration and evolution. Based on the theoretical connotation of business model and iterative innovation, the connotation concept of business model iteration is clarified in this paper. A business model iteration system under the energy Internet is constructed, and the business model iteration path covering "iteration basis, iteration demand, iteration objective, iteration strategy, and overall evaluation" is established, and the iteration mechanism and methods of each link are proposed. Based on the characteristics of energy Internet, the business model iteration system is used to explore the differential application of the iterative system, with focus on three major emerging businesses，including new business of energy transformation, new products of energy digitization and new service of energy platform. Through a case study of virtual power plant and multi-station integration business, a study is made in stage and step on the design and implementation methods of business model iteration. The proposed strategy and method can effectively guide the business model iterative design and perfection of emerging businesses under the energy Internet, and provide theoretical support for innovation and effectiveness verification of business models.